2013
DOI: 10.1186/2008-2231-21-27
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of Lumefantrine – Oleic acid self nanoemulsifying ionic complex for enhanced dissolution

Abstract: BackgroundLumefantrine, an antimalarial molecule has very low and variable bioavailability owing to its extremely poor solubility in water. It is recommended to be taken with milk to enhance its solubility and bioavailability. The aim of present study was to develop a Self Nanoemulsifying Delivery system (SNEDs) of lumefantrine (LF) to achieve rapid and complete dissolution independent of food-fat and surfactant in dissolution media.MethodsSolubility of LF in oil, co-solvent/co-surfactant and surfactant soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 15 publications
3
35
0
Order By: Relevance
“…Most of the tested formulations showed excellent self-emulsification in water, at pH 1.2, and even at pH 6.8. This observation is in agreement with recent studies (Larsen et al, 2012;Patel, Sarma, Vavia, 2013) where OL self-emulsifying formulations have exhibited excellent self-emulsification in all tested media. This promising OL characteristic might be explained by the low acid value of OL compared with other fatty acids ( Figure 5) leading to a decreased precipitation tendency at pH 6.8.…”
Section: Influence Of Internal Acidificationsupporting
confidence: 83%
See 2 more Smart Citations
“…Most of the tested formulations showed excellent self-emulsification in water, at pH 1.2, and even at pH 6.8. This observation is in agreement with recent studies (Larsen et al, 2012;Patel, Sarma, Vavia, 2013) where OL self-emulsifying formulations have exhibited excellent self-emulsification in all tested media. This promising OL characteristic might be explained by the low acid value of OL compared with other fatty acids ( Figure 5) leading to a decreased precipitation tendency at pH 6.8.…”
Section: Influence Of Internal Acidificationsupporting
confidence: 83%
“…Some articles showed droplet size increases upon drug incorporation (Kommuru et al, 2001;Kang et al, 2004), while a few articles showed no droplet size difference upon drug incorporation (Nielsen et al, 2007). However, one recent publication showed significant droplet size decrease upon drug incorporation (Patel, Sarma, Vavia, 2013). This last publication may be in agreement with the current work because it has also investigated a very similar formulation composition (OL/ medium chain monoglycerides/Cr-El) with a weakly basic drug (lumefantrine).…”
Section: Ol/i308/cr-el Systemsupporting
confidence: 80%
See 1 more Smart Citation
“…The recently published article in the esteemed journal entitled “Design and evaluation of Lumefantrine – Oleic acid self nanoemulsifying ionic complex for enhanced dissolution” [1], describes an in-depth research pertaining to the formulation attributes of lumefantrine, an important ani-malarial drug, to enhance its in vitro dissolution and thereby improving its bioavailability upon oral administration. As discussed by authors’ poor solubility of novel chemical entities (NCEs) leads to lack of in vivo translation of the promising in vitro attributes of NCEs because they fail to achieve adequate exposure needed to modulate the target or receptors under in vivo conditions [1].…”
Section: Dear Editor-in-chiefmentioning
confidence: 99%
“…As discussed by authors’ poor solubility of novel chemical entities (NCEs) leads to lack of in vivo translation of the promising in vitro attributes of NCEs because they fail to achieve adequate exposure needed to modulate the target or receptors under in vivo conditions [1]. Since lumefantrine has a low and variable bioavailability dependent on the food intake, it is extremely challenging to maintain the threshold levels of the drug needed to combat malarial infections [2].…”
Section: Dear Editor-in-chiefmentioning
confidence: 99%